Investigasi Penentu Kinerja Karyawan - Ainun Muawanah; Teguh Ariefiantoro; Aprih Santoso (POINT: Jurnal Ekonomi dan Manajemen, 2022)
Many factors can affect employee performance, such as Work Environment, Leadership, Training and Work Discipline. The purpose of the study was to analyze the effect of the work environment, leadership, training and work discipline on employee performance in the sales department of PT. Toyota Nasmoco Karangjati. This study uses a survey method to employees of the marketing department at PT. Toyota Nasmoco Karangjati has 33 employees as respondents. The sampling technique in this study is the saturated sample. The analytical tools used in this study are: validity test, reliability test, classical assumption test, heteroscedasticity test, ui coefficient of determination and multiple regression analysis. The results of this study indicate that the work environment has a positive and significant effect, giving the understanding that if the work environment is supportive, it will lead to morale. Leadership has a positive and significant effect, giving the understanding that a leader must have a strong individual concept and ability to achieve his goals in the company. Job training has a positive and significant effect, providing an understanding that training is necessary to improve the skills and performance of the company's work. Work Discipline has a positive and significant effect. Provide an understanding that the more disciplined an employee will be, the more the performance of the given employee will increase.